The Effects of Quizizz on Students’ Reading Ability and Learning Motivation in Indonesian EFL Classrooms - Akhyar, Muhammad Fuad; Roslaini, Roslaini (Journal of Language and Literature Studies, 2025)
This study explores the impact of Quizizz, a gamified learning platform, on students’ reading comprehension and learning motivation. The research focuses on ten reading subskills, including vocabulary, inference, and text structure, and investigates motivational outcomes through the lens of Self-Determination Theory, which encompasses autonomy, competence, and relatedness. Employing a quasi-experimental mixed-methods approach, the study involved 40 eleventh-grade students from SMA Muhammadiyah 11 Jakarta, equally assigned to experimental and control groups. Over a five-week period, the experimental group utilized Quizizz during instruction, while the control group received conventional teaching. Data were collected through reading comprehension tests and semi-structured interviews. Quantitative findings revealed a statistically significant improvement in the experimental group’s post-test scores, as measured by the Mann-Whitney U Test. Qualitative analysis indicated that Quizizz supported students’ autonomy through flexible learning, enhanced their competence via immediate feedback, and fostered relatedness through social interaction and friendly competition. These results suggest that integrating gamified tools like Quizizz can enhance both reading outcomes and student motivation in EFL classrooms. Implications for classroom practice highlight the potential for incorporating game-based learning into curriculum design to foster more engaging and effective literacy instruction.